Analysis of Factors Related to The Incidence of Pediatric Pulmonary Tuberculosis in Sibuhuan General Hospital - Fitriani Pramita Gurning; Eliska Eliska; Muchti Yuda Pratama (Universitas Airlangga, 2018)
Background: Pulmonary tuberculosis (TB) sufferers in Indonesia have dramatically increased from 1997 to 2014. The cases of pediatric pulmonary TB in Indonesia was firstly discovered in 2013, namely at the age of <1 year group about 2‰, 1-4 years group about 4‰, and 5-14 years group about 0.30‰. Purpose: This study aims to determine the factors associated with the incidence of pediatric pulmonary TB in Sibuhuan General Hospital. Methods: This study was conducted at Sibuhuan General Hospital, Padang Lawas Regency by using a cross-sectional study design. The population in this study were all children aged range from 0 to 5 years who came for treatment to the pulmonary clinic at Sibuhuan General Hospital which counting about 55 children. Data analysis in this study were used chi-square test. Results: The study showed that pediatric pulmonary TB patients occurred in the male group counting about 33 persons (60%), normal nutritional status group as many as 35 persons (63.60%), low socio-economic group counting about 32 persons (58.20%), never treated by BCG immunizations group counting about 32 persons (58.20%). Variables related to the incidence of pediatric pulmonary TB in Sibuhuan General Hospital were nutritional status (PR = 3.31; 95% CI = 1.83 <PR <5.98), socio-economic (PR = 5.51; 95% CI = 1.88 <PR <16.182) and BCG immunization (PR = 2.59; CI = 1.15 <PR <5.33). Conclusion: : Nutritional status, socio-economic status and BCG immunization significantly influence the incidence of pediatric pulmonary TB in Sibuhuan General Hospital.